Single-Component Revisions are Associated with Dislocation after Revision Total HIP Arthroplasty at Intermediate-Term Follow-Up. Issue 3 (16th May 2016) - Stedman, Roman C.; Lim, Daniel; Husain, Adeel; Courtney, Paul M.; Nelson, Charles L.
Purpose: Dislocation is the most frequent complication following revision total hip arthroplasty (THA). Although several risk factors for dislocation in revision THA have been described, many cannot be modified at the time of surgery. Identifying modifiable risk factors for subsequent dislocation after revision THA provides opportunity for orthopedic surgeons to decrease instability. Methods: A retrospective analysis of 203 consecutive revision THA procedures performed by a single surgeon with a minimum 2-year follow-up between May 2003 and June 2012 was performed. 2 (1.0%) died and 14 (6.9%) were lost to follow-up leaving 187 (92%) revision procedures in 123 men and 64 women. Univariate and multivariate logistic regression was used to identify risk factors for dislocation. Results: 9 (4.8%) of all patients reviewed experienced a dislocation episode. Of those, 8 (89%) had a single component revised, 6 (67%) were women, and 4 (44%) had a history of recurrent dislocation. 2 of 14 (14%) patients with a constrained liner dislocated. Univariate analysis demonstrated that single-component revisions were at higher risk for dislocation after the surgery (p value = 0.033). Conclusions: Identifying modifiable risk factors for dislocation after revision THA provide opportunity to decrease rates of instability. Based on our data, single-component revision THA is a risk factor for subsequent dislocation.